2020
DOI: 10.1111/bjop.12448
|View full text |Cite
|
Sign up to set email alerts
|

Ecological social capital does not predict geographical variance in increases in depression following the 2008 financial crisis

Abstract: Research suggests that the financial crisis of 2008 and its aftermath were associated with an increase in mental health problems, but there has been little research into potential protective factors. Ecological social capital is a plausible candidate given evidence of its protective status following natural disasters. Pre‐crisis area‐level estimates of generalized trust and sense of belonging were computed from the 2004 to 2006 waves of the Living in Wales survey (N = 43,473) for 413 neighbourhoods in Wales, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This avoids the problems associated with using small and unrepresentative local samples, but it is not clear that country-level estimates of social capital are good proxies for the ecological social capital experienced by any given citizen. There is a striking variation in ecological social capital at the neighbourhood level, 4 14–16 which country-level estimates do not capture. Even the previous studies that used sub-national geographical units, 8 12 looked at social capital on the levels of counties, and in some cases entire states, rather than neighbourhoods.…”
mentioning
confidence: 96%
“…This avoids the problems associated with using small and unrepresentative local samples, but it is not clear that country-level estimates of social capital are good proxies for the ecological social capital experienced by any given citizen. There is a striking variation in ecological social capital at the neighbourhood level, 4 14–16 which country-level estimates do not capture. Even the previous studies that used sub-national geographical units, 8 12 looked at social capital on the levels of counties, and in some cases entire states, rather than neighbourhoods.…”
mentioning
confidence: 96%
“…The reviews included a total of 322 different identifiable studies, of which 52 were included in more than one review (although Martin-Carrasco reported using evidence from a total of 354 studies, but detailed data was only extracted from 69). In addition, we identified nine further peer-reviewed primary studies (Alvarez-Galvez et al 2021, Aretz 2022, Cherrie et al 2021, Clair & Baker 2022, Kim et al 2022, Saville 2021, Wickham et al 2020) and two reports from grey literature (Clark & Wenham 2022, Office for National Statistics 2022.…”
Section: Overview Of the Evidence Basementioning
confidence: 99%
“…Seven of the additional primary studies (Cherrie et al 2021, Clair & Baker 2022, Kim et al 2022, Saville 2021, Wickham et al 2020 were conducted in the UK. The remaining two primary studies were in other European countries (Alvarez-Galvez et al 2021, Aretz 2022.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The results are reminiscent of work comparing the Finnish-speaking majority and Swedishspeaking minority in Finland [41], where the better health of Swedish minority is partly attributable to greater social capital. This is also a possibility in Wales, where geographical variability in social capital favours some of the rural areas where Welsh speakers predominantly live, and is particularly low in the South Wales Valleys [20,21]. More broadly, degree of cultural assimilation or cultural distinctiveness has been shown to be related to health in Japanese-Americans [23] and, potentially, these differences represent something similar.…”
Section: Possible Mechanismsmentioning
confidence: 99%
“…Rurality has been associated with better mental health in the UK [18] but may also lead to adverse consequences due to poorer access to healthcare [19]. Large geographical disparities also exist in ecological social capital, the presence of and access to resources embedded in social networks in a given locality, and these have also been associated with health outcomes [20,21]. Thirdly, as described above, even explicitly civic national identities are often related to cultural, linguistic and other ethnic characteristics and such characteristics are often related to population health [22][23][24].…”
Section: Introductionmentioning
confidence: 99%